APPLICATION OF COLLAGE MEDIA IN IMPROVING FINE MOTORCYCLE IN GROUP A TK. ABA 17 MEDAN - Indah Cahyani S, Regita; Lubis, Faizal (Proceeding International Seminar of Islamic Studies, 2022)
Improving the quality of Early Childhood Education, teachers must have high creativity in delivering material using methods that make children motivated to learn. One of them is the collage method which aims to improve fine motor skills in early childhood. This study uses qualitative and descriptive methods with data collection techniques by observation, interviews, and documentation. The subjects of this study consisted of 1 homeroom teacher, and 7 students of group A kindergarten. ABA 17 Medan. The purpose of this study was to determine the fine motor development of children through collage activities in kindergarten. ABA 17 Medan. The results showed that in the collage activity there were several active children and children who were less active in carrying out these activities. It is hoped that kindergarten teachers After this research is carried out, there is a need for a deep teaching intensity for children's motor development at the school. One of them is by using collage activities and it can also use natural material media to improve the fine motor skills of early childhood.